Party Support to Social Movements: An Electoral-Oriented Strategy?. Issue 2 (2nd July 2016) - Piccio, Daniela R.
Abstract : The main objective of this article is to explore the logic underlying party support to social movements. Do political parties respond to social movements only when electoral incentives are at stake, as movements' activists have often lamented and rational-oriented scholarly approaches have maintained? This article tackles this question reconstructing the conditions that led the Dutch Social Democratic party to turn supportive to the social movements' mobilisations at the time of the 'participatory revolution' decades. The analysis will show that not the competitive environment but rather the internal organisational characteristics of the party are the strongest predictor in explaining the party's openness to the movements. Beyond this specific case, the article provides additional empirical backing to research on party change; shows that rational-oriented perspective can disguise the processes by which events take place and distort their meaning; points to social movements as important stimuli for political parties to change, incorporate new ideas and provide linkage with the citizens.